2024
DOI: 10.32391/ajtes.v8i1.381
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Open Rives-Stoppa Procedure in Complex Incisional Hernia.

Bledi Masati,
Asfloral Haxhiu,
Marsel Dhima
et al.

Abstract: Introduction: Ventral hernia is one of the most common general surgical pathologies. An incisional hernia will develop in 10–15% of patients with an abdominal incision, and the risk increases to up to 23% in those who develop surgical site infections. Ventral hernia repairs are mostly elective (90%) procedures, but the repair methods are highly variable. Popularized in Europe by Rives and Stoppa, the retromuscular technique has proven to be very effective, with a 94.2% probability of having the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Extensive studies have consistently demonstrated that this method yields excellent long-term outcomes with remarkably low morbidity rates, particularly in patients with large primary or recurrent incisional hernias. This establishes it as the gold standard for many surgeons [23]. Characterized by a retromuscular approach, the Rives-Stoppa procedure has proven highly effective, boasting a high likelihood of achieving the lowest odds for both recurrence and surgical site infections (SSI) [23].…”
Section: Advantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive studies have consistently demonstrated that this method yields excellent long-term outcomes with remarkably low morbidity rates, particularly in patients with large primary or recurrent incisional hernias. This establishes it as the gold standard for many surgeons [23]. Characterized by a retromuscular approach, the Rives-Stoppa procedure has proven highly effective, boasting a high likelihood of achieving the lowest odds for both recurrence and surgical site infections (SSI) [23].…”
Section: Advantagesmentioning
confidence: 99%
“…This establishes it as the gold standard for many surgeons [23]. Characterized by a retromuscular approach, the Rives-Stoppa procedure has proven highly effective, boasting a high likelihood of achieving the lowest odds for both recurrence and surgical site infections (SSI) [23]. Moreover, a modified version of the Rives-Stoppa repair has notably reduced recurrence rates and complications, with only a minimal proportion of patients experiencing recurrent incisional hernias [23].…”
Section: Advantagesmentioning
confidence: 99%
See 1 more Smart Citation